Analyzing the Students' Development Management to Enforce the Discipline at Private Islamic Junior High School Pati Regency, Indonesia - Haryanto Haryanto; Nur Khoiri; Latisha Asmaak Shafie (Badan Litbang dan Diklat Kementerian Agama RI, 2026)
This study analyzes student development management in enforcing discipline at MTs Swasta Dukuhseti, Pati Regency. Using a qualitative single-case study design, data were collected through interviews, observations, and document analysis involving 15 informants. The findings show that student management is implemented through participatory planning, tiered implementation involving teachers and dormitory supervisors, and monthly evaluations. Discipline enforcement is based on three pillars: integration of Sharia-based religious values, a transparent reward-and-punishment Point System, and active support from the school committee and foundation. Student classroom compliance reached 93%, while overall violations decreased from 10% to 7%. Challenges include limited human resources, heavy teacher workloads, and diverse student backgrounds. The study highlights that effective discipline in private madrasahs should move from formal external compliance toward internalized religious self-awareness, supported by visionary leadership, exemplary behavior, and strong collaboration between schools, foundations, and parents. AbstrakPenelitian ini menganalisis manajemen pembinaan kesiswaan dalam penegakan disiplin di MTs Swasta Dukuhseti, Kabupaten Pati. Penelitian menggunakan pendekatan kualitatif studi kasus tunggal dengan pengumpulan data melalui wawancara, observasi, dan analisis dokumen terhadap 15 informan. Hasil penelitian menunjukkan bahwa pembinaan kesiswaan dilaksanakan melalui perencanaan partisipatif, pelaksanaan berjenjang yang melibatkan guru dan pembina asrama, serta evaluasi bulanan. Penegakan disiplin berpusat pada tiga pilar, yaitu integrasi nilai religius berbasis syariah, sistem penghargaan dan sanksi melalui Point System yang transparan, serta dukungan aktif dari komite sekolah dan yayasan. Tingkat kepatuhan siswa mencapai 93%, sementara pelanggaran menurun dari 10% menjadi 7%. Tantangan yang dihadapi meliputi keterbatasan sumber daya manusia, tingginya beban kerja guru, dan keberagaman latar belakang siswa. Penelitian ini menegaskan bahwa disiplin yang efektif di madrasah swasta perlu diarahkan dari kepatuhan formal menuju kesadaran religius internal melalui kepemimpinan visioner, keteladanan, dan sinergi antara madrasah, yayasan, dan orang tua.